Zastosowanie demograficznych modeli wielokrotnego ubytku w kalkulacji składek w ubezpieczeniach na życie - Wieteska, Stanisław (Application of demographical multiple decrement models in calculation of life insurance's premium, 2006)
Multiple decrement models of are important part of demographical mathematics. Decrements (as a cause of decrease of population) and calculated on their basis probabilities of demise, survival or intensity of dying out can be used to calculate life insurance’s premium. In this paper an example of using decrements in such a way is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 557-566